Unpartnered Mothers’ Work–Family Conflict and Parenting Stress: The Moderating Effects of Nonstandard Work Schedules - Hwang, Woosang (J Fam Econ Issues, 2019)
Using the Fragile Families and Child Wellbeing Study dataset, we examined the moderating effects of nonstandard work schedules on the association between work-family conflict and parenting stress among unpartnered mothers one year after childbirth. A multiple-group analysis was conducted to examine the interaction between a latent continuous variable (work-family conflict) and observed categorical variables (four types of work schedules: daytime weekday, daytime weekend, nighttime weekday, and nighttime weekend). Results showed that unpartnered mothers’ work-family conflict was positively associated with their parenting stress, regardless of their work schedules. In addition, unpartnered mothers’ nonstandard work schedules moderated the association between work-family conflict and parenting stress. Contrary to our expectations, however, the negative effects of work-family conflict on parenting stress were alleviated in unpartnered mothers who worked nighttime compared to those who worked daytime weekend. This result indicates that working nights can be a strategy by which unpartnered mothers can balance work and family life. Specifically, using informal caregiving support, unpartnered mothers can have a respite from parenting by working nonstandard hours. Implications are discussed in terms of the importance of researchers’ and policymakers’ attention regarding unpartnered mothers’ work and parenting issues.